A transition metal-catalyzed enyne metathesis for the preparation of pyrrolizidine alkaloid core: Application towards the total synthesis of stemaphylline. (30th March 2021) - Kumar, Praveen; Rahman, Md. Ataur; Haque, Ashanul; Singh Yadav, Jhillu
Graphical abstract: Highlights: Synthesis of of pyrrolizidine alkaloid core and its application towards stemaphylline. Ru-catalyzed ring closing enyne metathesis (RCEM). Effect of catalysts, solvents and temperature were screened. Abstract: In this paper, we disclose an efficient route for the synthesis of pyrrolizidine alkaloid core and its application towards the total synthesis of stemaphylline. The key pyrrolizidine core was achieved with Ru-carbene catalyzed ring closing enyne metathesis (RCEM). The effect of different types and amounts of Ru-carbene catalysts, solvents and temperature were systematically studied. The advantage of this method includes the construction of pyrrolizidine alkaloid core in a single operation.